Analisis Ketersediaan dan Kelayakan Sarana Prasarana dalam Mendukung Desa Wisata Nagari Sumpur, Kabupaten Tanah Datar, Sumatera Barat sebagai Destinasi Ekowisata Berkelanjutan - Sri Muthia Hasan; Asima Tiara Agnesia Pasaribu; Khairani Aprilia; Rosma Purba (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2025)
This study aims to analyze the availability and feasibility of tourism infrastructure in Nagari Sumpur, West Sumatra, in supporting the development of a sustainable ecotourism-based village. The research employs a qualitative descriptive approach, with data collected through field observations and in-depth interviews. The findings indicate that Nagari Sumpur has promising infrastructure potential, particularly in basic facilities such as road networks and clean water supply, as well as natural and cultural attractions. However, several challenges persist, including limited supporting facilities (public toilets, tourist information centers, and telecommunication networks), suboptimal waste management systems, and a lack of renewable energy facilities. Strategic recommendations are formulated in three phases: short-term (improvement of basic facilities), medium-term (enhancement of technological infrastructure and environmental management), and long-term (implementation of eco-friendly technology and human resource development). This study contributes to sustainable village tourism development by emphasizing the importance of balancing environmental, economic, socio-cultural, and sustainability management aspects.